Development of a petrographic technique to assess the spontaneous combustion susceptibility of Indian coals - Mohalik, N.K.; Lester, E.; Lowndes, Ian (Taylor & Francis, 2017)
Petrographic studies are commonly used categorise the potential utilisation of coals. Eleven coal samples from the jharia coalfield (JCF), india, were studied using petrographic techniques to investigate maceral content, reflectance, and textural characteristics. Multiple test samples of each coal were slowly oxidised under controlled laboratory conditions from an ambient temperature of 30°c to 300°c to investigate the morphology of oxidised coals. The petrographic characterisation of the coals before and after oxidation showed important changes in both morphology and vitrinite reflectance. The oxidation of the coal particles produced three predominant textural changes: particles with homogeneous change of reflectance (HCv), particles with oxidation rims (ORv), and particles with no changes were observed (Uv) respectively. These textural characteristics were used to indicate how particles had interacted with oxygen at low temperatures during the early stages of oxidation. The morphological classification developed provides an alternative method to confirm the susceptibility of a coal to spontaneous combustion. Conventional thermal parameters such as crossing point temperature (CPT) were unable to identify the coals prone to spontaneous combustion. However, certain petrographic parameters could be combined with CPT values to provide a much more accurate measure for susceptibility to spontaneous combustion.